DISTAL TIBIAL RECONSTRUCTION WITH INTRAMEDULLARY NAIL COMBINED WITH T-PLATE FOLLOWING EN-BLOC-EXCISION OF GIANT CELL TUMOR OF DISTAL TIBIA: CASE-REPORT - Mujaddid Idulhaq; Fajar Baskoro Gardjito; Ibnu Yudistiro (Journal Orthopaedi and Traumatology Surabaya)
Background: Giant cell tumor is locally aggressive benign tumor that occur more common in distal femur, proximal tibia, and distal radius, and has tendency for recurrence and has capability for metastatize. Giant cell tumor in foot ankle are rare, and comprise less than four percent of giant cell tumor of the bone.